Software Modification in a Fault Analysis Tool for Critical Path Debugging - Han, Chung Dean (2009)
Microprocessor units caught with speed failure are becoming more and more eminent as the fabrication process shrinks according to Moore’s Law. Failure Analysis (FA) engineers confront the problem using Critical Path Debug method utilizing special IC (Integrated Circuit) test system capable of testing various types of microprocessor’s failure. But such test system does not come cheap, each costing more than USD 2.5 million. In order to bring down cost, a system to pull test data and locate critical path using personal computer (PC) is proposed. This system is built upon Intel Penang’s Internal FA tool called Personal Computer Failure Analysis (PCFA) which utilizes a host computer to collect data from Device Under Test (DUT) through TAP (Test Access Port). As PCFA was not originally build up to carry out critical path debug, hardware modification and software enhancement is required. The hardware modification involves platform rework and external FSB (Front Side Bus) frequency injection. By doing so, microprocessor speed can be controlled during test pattern run. The software is modified to include critical-path-related test subroutines housed inside PCFA library. These subroutines collect, compare and display test results. The program is tested with a series of Intel’s microprocessors to ensure that it is working as intended for current and future products. 1000 test vector results are recorded from both PCFA and ATE’s system to carry out compare verification.100% matched is observed for all the test vector results thus prove the functionality of the project “Critical Path Fault Isolation Debug for Intel Microprocessor Using Personal Computer”. The PCFA hardware cost only USD 10 thousand which is 0.4% of the cost of an IC test system and is currently capable of running shmoo, performing cache test, I/O pin test and also macro Fault Isolation (FI) for each test pattern in a couple of seconds. Although in terms of functionalities; complex IC test system will certainly have the upper hand but in the case of solving common general microprocessors’ failures, system based test solution is much more cost effective.